Brouwer's Fixed Point Theorem with Isolated Fixed Points and His Fan Theorem. (26th January 2012) - Tanaka, Yasuhito
Abstract : We show that Brouwer's fixed point theorem with isolated fixed points is equivalent to Brouwer's fan theorem.